Impact of cyclodextrins on the behavior of amphiphilic ligands in aqueous organometallic catalysis - Bricout, Hervé; Léonard, Estelle; Len, Christophe; Landy, David; Hapiot, Frédéric; Monflier, Eric (Beilstein Journal of Organic Chemistry, 2012)
In this study, we showed that the addition of randomly modified β-cyclodextrin (RAME-β-CD) in aqueous medium could have a beneficial impact on the catalytic performances of phosphane-based aggregates in the Pd-catalyzed cleavage of allyl carbonates (Tsuji–Trost reaction). The RAME-β-CD/phosphane supramolecular interactions helped explain the catalytic results. The presence of RAME-β-CD in the aqueous compartment improved the phosphane-based aggregate dynamics. The exchanges between the hydrophobic substrate-containing aggregate core and the catalyst-containing aqueous phase were then greatly favored, resulting in an increase in the catalytic performances.
Keywords: amphiphilic phosphanes; biphasic system; cyclodextrins; micelles